Analysis of differential gene expression by display of 3' end restriction fragments of cDNAs. - Prashar, Y (1996)
We have developed an approach to study changes in gene expression by selective PCR amplification and display of 3' end restriction fragments of double-stranded cDNAs. This method produces highly consistent and reproducible patterns, can detect almost all mRNAs in a sample, and can resolve hidden differences such as bands that differ in their sequence but comigrate on a gel. Bands corresponding to known cDNAs move to predictable positions on the gel, making this a powerful approach to correlate gel patterns with cDNA data bases. Applying this method, we have examined differences in gene expression patterns during T-cell activation. Of a total of 700 bands that were evaluated in this study, as many as 3-4% represented mRNAs that are upregulated, while approximately 2% were down-regulated within 4 hr of activation of Jurkat T cells. These and other results suggest that this approach is suitable for the systematic, expeditious, and nearly exhaustive elucidation of subtle changes in the patterns of gene expression in cells with altered physiologic states.